(3bUjOI deMeO Hf YeQs - (3eMeO Hf YeQs
(3ChdgG (B:s
(3bGd eMeO gh GHf YeQ MeOkG de HGdYde bdHG YeQG s
(3BNQgG (B:s
(3hGLYd OhGAgG HbOQ GdOGA aEfge cGdNjW aj GdghGA aj Ndjd cWjH Je GdeQGO aGage GdeQGOG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGdKs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg eGdc (B411) s
Keywords: (3Gdabg GdeGdcjs